Estudos de pré-formulação de cápsulas gelatinosas duras contendo formulação de extrato de Gymnema sylvestre em pó - Carbinatto, F. M. [UNESP]; Castro, Ana Doris de [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Silva, Jr. (My University, 2011)
Gymnema sylvestre extract (GSE) is a plant product widely used as an adjuvant in the treatment of diabetes mellitus and commercially available as a powder. Owing to its low flowability, the manufacturing of hard gelatin capsules containing GSE faces specific problems. The purpose of this study was to investigate the best excipient (starch, lactose or microcrystalline cellulose) for hard gelatin capsules containing GSE. The technological properties such us bulk density (ρβ); tapped density (ρt); inter-particle porosity (Ie); Carr index (CI); Hausner ratio (HR); loss on drying (%LOD) and particle size distribution (%Pf) of the various GSE mixtures were investigated with the aim of identifying the best excipient. The need for lubricants (talc/magnesium stearate) was also assessed. GSE was characterized as a fine powder with more than 50% of its particles between 0.149mm to 0.250mm; furthermore, CI=25.6%; RH=1.3 and Ie = 25.6% and, as expected with such properties, it showed poor flowability. All the excipients investigated were able to change the technological properties of GSE and the powder mixture containing microcrystalline cellulose gave the best results.

Estudos de pré-formulação de cápsulas gelatinosas duras contendo formulação de extrato de Gymnema sylvestre em pó O extrato seco de Gymnema sylvestre (EGS) é um produto fitoterápico amplamente utilizado como adjuvante no tratamento da diabetes, sendo comercializado na forma de pó. O objetivo do presente estudo foi investigar a influência da adição de adjuvantes (amido, lactose ou celulose microcristalina) à formulação para a preparação de cápsulas gelatinosas duras contendo o EGS. As propriedades tecnológicas como densidade aparente (Da), densidade aparente de compactação (Dc), porosidade interparticulas (Ie), Índice de Carr (IC), Fator de Hausner (FH), perda por dessecação (PD%) e análise do tamanho de partículas (%Pf) das diferentes misturas preparadas foram investigadas com o objetivo de escolher o melhor excipiente. A necessidade de agentes lubrificantes (talco/estearato de magnésio) também foi avaliada. O EGS foi caracterizado como um pó fino, com mais de 50% do material particulado compreendido entre 0,149-0,250mm; IC=25,6%; FH=1,3 and Ie = 25,6%, o que justifica seu fluxo pobre. Todos os excipientes testados foram capazes de modificar as propriedades tecnológicas do EGS, sendo a mistura de pós que apresentou melhores resultados aquela obtida com a adição de celulose microcristalina.
Preformulation studies of Gymnema sylvestre extract powder formulation for hard gelatin capsules
Keywords: Gymnema sylvestre; Hard gelatin capsules; Preformulation studies; Solid dosage forms; Technological properties; Gymnema sylvestre extract; lactose; magnesium stearate; microcrystalline cellulose; starch; talc; bulk density; capsule filling; comparative effectiveness; drug capsule; drug coating; drug distribution; drug formulation; drug synthesis; intermethod comparison; nonhuman; particle size; porosity